The therapeutic value of yoga in neurological disorders - Mishra, Shri K. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: The ancient mind and body healing methods of yoga recently sparked fervor in the scientific community as an alternative and complementary means of therapy. Since the World Health Organization officially began promoting yoga in developing countries in 1978, yoga has been cited for its therapeutic potential and has been widely recognized in Western culture. However, as an increasing number of people practice yoga for remedial purposes, researchers raise two important questions: 1) Is yoga a valid complementary management and rehabilitation treatment modality? 2) What conditions show promise of treatment with this intervention?. OBJECTIVE: This review article uses comprehensive scientific, evidence-based studies to analyze the efficacy of various basic and applied aspects of yoga in disease prevention and health promotion. It specifically intends to expose the effects of yoga in neurological disorders, particularly epilepsy, stroke, multiple sclerosis, Alzheimer's disease, peripheral nervous system disease, and fibromyalgia. MATERIALS AND METHODS: Information was gathered from various resources including PubMed, Ovid, MD-Consult, USC, and U.C.L.A. libraries. Studies were selected and reviewed on the basis of sample size, control, randomization, double-blinding, and statistical analysis of results. RESULTS: The pratice of yoga and meditation demonstrates statistically encouraging physiological and psychological improvements in the aforementioned neurological disorders. However, there were certain flaws and inadequacies in the study designs employed to evaluate the same. A critical analysis of these studies is presented. CONCLUSIONS: With the aim to focus attention on this widespread yet largely unexamined treatment modality, this paper seeks to provide direction and support for further research necessary to validate yoga as an integrative, alternative, and complementary therapy.